The Effects of Interspersed Retrieval Practice in Multiple-List Learning on Initially Studied Material - Kliegl, Oliver; Kriechbaum, Verena M.; Bäuml, Karl-Heinz T. (Frontiers in Psychology, 2022)
The forward testing effect (FTE) refers to the finding that retrieval practice of previously studied material can facilitate retention of newly studied material more than does restudy of the material. The goal of the present study was to examine how such retrieval practice affects initially studied, unpracticed material. To this end, we used two commonly applied versions of the FTE task, consisting of either three (Experiment~1) or five (Experiment~2) study lists. While study of list 1 was always followed by an unrelated distractor activity, study of list 2 (3-list version) or lists 2, 3, and 4 (5-list version) was followed by either interim restudy or retrieval practice of the immediately preceding list. After studying all lists, subjects were either asked to recall the first or last study list. Results showed that, for both the three-list and five-list versions, interim retrieval practice led to a typical FTE, irrespective of whether unrelated or categorized study lists were used. Going beyond the prior work, interim retrieval practice was found to have no effect on initially studied, unpracticed material, regardless of the type of study material. The findings suggest that using interim retrieval practice as a study method can improve recall of the last studied list without incurring a cost for the initially studied material. Our results are difficult to align with the view that retrieval practice induces context change, but are consistent with the idea that retrieval practice can lead subjects to employ superior encoding strategies.